Stronger increase of methane emissions from coastal wetlands by non‐native Spartina alterniflora than non‐native Phragmites australis - Andrea Fuchs; Ian C. Davidson; J. Patrick Megonigal; John L. Devaney; Christina Simkanin; Genevieve L. Noyce; Meng Lu; Grace M. Cott (Plants, People, Planet)
Societal Impact Statement The invasive species S. alterniflora and P. australis are fast growing coastal wetland plants sequestering large amounts of carbon in the soil and protect coastlines against erosion and storm surges. In this global analysis, we found that Spartina and Phragmites increase methane but not nitrous oxide emissions, with Phragmites having a lesser effect. The impact of the invasive species on emissions differed greatly among different types of native plant groups, providing valuable information to managers and policymakers during coastal wetland planning and restoration efforts. Further, our estimated net emissions per wetland plant group facilitate regional and national blue carbon estimates. Summary Globally, Spartina alterniflora and Phragmites australis are among the most pervasive invasive plants in coastal wetland ecosystems. Both species sequester large amounts of atmospheric carbon dioxide (CO2) and biogenic carbon in soils but also support production and emission of methane (CH4). In this study, we investigated the magnitude of their net greenhouse gas (GHG) release from invaded and non‐invaded habitats. We conducted a meta‐analysis of GHG fluxes associated with these two species and related soil carbon content and plant biomass in invaded coastal wetlands. Our results show that both invasive species increase CH4 fluxes compared to uninvaded coastal wetlands, but they do not significantly affect CO2 and N2O fluxes. The magnitude of emissions from Spartina and Phragmites differs among native habitats. GHG fluxes, soil carbon and plant biomass of Spartina‐invaded habitats were highest compared to uninvaded mudflats and succulent forb‐dominated wetlands, while being lower compared to uninvaded mangroves (except for CH4). This meta‐analysis highlights the important role of individual plant traits as drivers of change by invasive species on plant‐mediated carbon cycles.